2017
DOI: 10.1099/jgv.0.000954
|View full text |Cite
|
Sign up to set email alerts
|

The cellular endosomal protein stannin inhibits intracellular trafficking of human papillomavirus during virus entry

Abstract: Human papillomaviruses (HPVs) are the most common sexually transmitted viruses and one of the most important infectious causes of cancers worldwide. While prophylactic vaccines are effective against certain strains of HPV, established infections still cause deadly cancers in both men and women. HPV traffics to the nucleus via the retrograde transport pathway, but the mechanism of intracellular transport of non-enveloped viruses such as HPV is incompletely understood. Using an overexpression screen, we identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…The formation of multivesicular bodies (MVBs) result in the sorting and subsequent disassembly of the HPV capsid. This is followed by endosomal escape of the L2/vDNA complex, where it is translocated to the host cell nucleus [ 30 , 157 ]. Factors regulating endosomal escape and post-endocytosis trafficking of high-risk HPVs are also potential targets of HPV infection and can be exploited to inhibit infection.…”
Section: Molecular Targets Of Early Hpv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of multivesicular bodies (MVBs) result in the sorting and subsequent disassembly of the HPV capsid. This is followed by endosomal escape of the L2/vDNA complex, where it is translocated to the host cell nucleus [ 30 , 157 ]. Factors regulating endosomal escape and post-endocytosis trafficking of high-risk HPVs are also potential targets of HPV infection and can be exploited to inhibit infection.…”
Section: Molecular Targets Of Early Hpv Infectionmentioning
confidence: 99%
“…Stannin, an 88-residue transmembrane protein, has been proposed to affect HPV16-PsV infection in a similar manner to HD5. Using an overexpression genetic screen for genes that affect HPV16-PsV infection, the SNN gene was identified that resulted in about a 50% decrease in HPV5, 16 and 18-PsV infection in vitro [ 157 ]. Moreover, SNN deficient mutant cell lines resulted in a 50% increase in HPV16-PsV infection to that of their wildtype counterparts [ 157 ].…”
Section: Molecular Targets Of Early Hpv Infectionmentioning
confidence: 99%
“…Stannin is another small endosomal transmembrane protein that has been shown to reduce HPV-16, HPV-18, and HPV-5 virus infection without affecting virus uptake or virus uncoating, but instead blocking virus entry into the TGN by routing the cargo to lysosomal compartments for degradation. Stannin overexpression reduces L2 and VPS35 co-localization, suggesting that it abrogates L2-retromer binding, a critical step for L2/vDNA to enter the TGN [ 64 ]. Gamma (γ)-Secretase also happens to play a vital role in successful HPV entry.…”
Section: Egress From the Late Endosome And Entry Into The Tgnmentioning
confidence: 99%
“…As discussed above, many host proteins and pathways are expoited by HPV to facilitate virion trafficking and viral infection, but some proteins can restrict HPV infection suggesting an inherent anti-papillomaviral function. The endosomal protein stannin restricts HPV infection by rerouting virions away from the TGN to degradative compartments [ 93 ]. Similarly, the α-defensin HD5 alters L2/vDNA trafficking, accelerating the degradation of virions within LE/lysosomal compartments to restrict HPV infection [ 94 ].…”
Section: Insertion and Protrusion Of L2mentioning
confidence: 99%
“…Similarly, the α-defensin HD5 alters L2/vDNA trafficking, accelerating the degradation of virions within LE/lysosomal compartments to restrict HPV infection [ 94 ]. Stannin appears to work by blocking association of L2 with retromer, to prevent retrograde trafficking of L2/vDNA, causing an increased accumulation of L2/vDNA in LAMP1-positive lysosomal compartments [ 93 ]. This is in contrast to retromer knockdown or mutation of retromer binding sites in L2, which instead cause a trafficking block within EEA1-positive endosomal compartments [ 48 ].…”
Section: Insertion and Protrusion Of L2mentioning
confidence: 99%